Carchemish in context: the Land of Carchemish Project, 2006-2010 - Wilkinson, Tony J.; Peltenburg, Edgar J.; Wilkinson, Eleanor Barbanes (Themes from the ancient Near East BANEA publication series, 2016)
Introduction / T.J. Wilkinson and Edgar Peltenburg -- Sketch history of Karkamish in the earlier Iron Age Iron I-IIB / J.D. Hawkins and M. Weeden -- The land of Carchemish and its neighbours during the Neo-Hittite period (c. 1190-717 BC) / Michael Brown and Stefan Smith -- Long-term settlement trends in the Birecik-Carchemish sectors / Dan Lawrence and Andrea Ricci -- The landscapes of Carchemish / T.J. Wilkinson -- The scent of empire on the Sajur / Jesper Eidem -- Carchemish in the 3rd millennium : a view from neighbouring Tell Jerablus Tahtani / Edgar Peltenburg -- Investigations of Iron Age Carchemish : the outer town survey of 2009 and 2010 / Eleanor Wilkinson and Andrea Ricci -- The Carchemish region between the Hellenistic and early Islamic periods / Paul Newsom -- Sixty years of site damage in the Carchemish region / Emma Cunliffe -- Discussion / T.J. Wilkinson and Edgar Peltenburg -- Appendix A: The Land of Carchemish Survey (Syria), 2006-2010 : site gazetteer / T.J. Wilkinson, Dan Lawrence and Andrea Ricci
"British Association for Near Eastern Archaeology (BANEA). - Includes bibliographical references. - Description based on print version record and CIP data provided by publisher; resource not viewed
Includes bibliographical references
Keywords: Land of Carchemish Project; Karkamiş Region (Turkey) -- Antiquities; Jarābulus Region (Syria) -- Antiquities; Carchemish (Extinct city); Turkey; Carchemish (Extinct city); Electronic book; Electronic books; Ausgrabung; Karkemisch